Gαi1/3 signaling mediates IL-5-induced eosinophil activation and type 2 inflammation in eosinophilic chronic rhinosinusitis - Xie, Huanxia; Ji, Jiang; Liu, Zhichen; Lu, Ning; Wei, Yuqian; Zhou, Aina; Liu, Jisheng; Jiao, Qingqing (Frontiers in Immunology, 2025)
BackgroundUncontrolled severe eosinophilic chronic rhinosinusitis (eCRS) is associated with elevated levels of Th2 cells and raised immunoglobulin concentrations in nasal polyp tissue. eCRS is characterized by high eosinophilic infiltration and type 2 inflammation. Gαi1/3 proteins participate in allergic inflammation by regulating immune cells. Whether Gαi1/3 proteins have a role in the development of eCRS remains unknown.ObjectivesTo investigate the association between Gαi1/3 expression levels and CRS and the underlying mechanismsMethodsWestern blotting and immunohistology were used to detect Gαi1/3 expression. Correlations between Gαi1/3 and immune cells and clinical parameters were analyzed. Signaling pathway activation in IL-5-induced Gαi1/3-knockout or knockdown mouse embryonic fibroblasts (MEFs) and eosinophils (EoL-1 cells) was detected by western blotting. EdU/DAPI was used to evaluate the proliferation of EoL-1 cells. A CRS model was established using Gαi1/3-knockout mice, and histological analysis and inflammatory cytokine measurements were performed.ResultsCompared with the non-eCRS subset, the eCRS subset showed significantly increased Gαi1/3 expression levels. High nasal tissue Gαi1/3 levels were linked to high tissue eosinophil infiltration, and high disease severity and allergic conditions in CRS patients. Gαi1/3 were required for IL-5-induced Akt-mTOR and Erk activation in MEFs. In EoL-1 cells, Gαi1/3 was associated with IL-5-activated IL-5Rα, promoting IL-5Rα endocytosis and transducing downstream signaling. IL-5-induced EoL-1 cell proliferation and degranulation were suppressed after Gαi1/3 silencing. In a CRS murine model, immune cell infiltration and type 2 inflammation were largely impaired in Gαi1/3-double-knockout mice.ConclusionIncreased Gαi1/3 expression levels in nasal tissue are linked to eosinophil infiltration and increased disease severity in CRS patients. Gαi1/3 contributes to eosinophil activation and participates in regulating allergic inflammation in CRS patients.